Cover Feature: Selective One‐Pot Two‐Step C−C Bond Formation using Metal–Organic Frameworks with Mild Basicity as Heterogeneous Catalysts (ChemCatChem 21/2017). Issue 21 (9th November 2017) - Cirujano, Francisco G.; López‐Maya, Elena; Rodríguez‐Albelo, Marleny; Barea, Elisa; Navarro, Jorge A. R.; De Vos, Dirk E.
Abstract : The Cover Feature shows a tandem two‐step C−C bond formation catalyzed by a new copper ion exchanged metal‐organic framework (MOF) with high basicity and stability. In their Communication, F. G. Cirujano, E. López‐Maya et al. describe how to selectively direct the tandem C−C bond formation towards the desired pharmaceutical intermediate by tuning the basicity of defective nickel pyrazolate frameworks, through ion exchange with Cu(II) cations. The presence of copper ions at the nickel‐oxo clusters and the adequate basicity of this MOF promote the selective condensation and alkylation steps, directing the benzaldehyde starting product towards the substituted indole and minimizing the formation of by‐products. More information can be found in the Communication by F. G. Cirujano, E. López‐Maya et al. onpage 4019 in Issue 21, 2017 (DOI:10.1002/cctc.201700784 ).